2009
DOI: 10.3923/pjbs.2009.1237.1245
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intra-Hippocampal Injection of Growth Hormone on Spatial Learning and Memory in Animal Model of Alzheimer’s Disease

Abstract: The aim of this study was to evaluate the effect of intra-hippocampal injection of Growth Hormone (GH) on impaired spatial cognition in rats with Alzheimer's Disease (AD). Growth hormone replacement therapy leading to improved cognition and well-being has mainly been carried in GH-deficient patients. Nevertheless, relatively only a few studies have investigated the function of GH in the brain. Aged Wistar male rats (350-400 g, 18-20 months old) were randomly divided into 6 groups (7 in each): Control (healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Our primary keyword search produced the article (Malek et al, 2009) on the somatotropin-based treatment of some complications of sporadic AD (Turnaev et al, 2016). In addition, our secondary keyword search yielded a lot of articles on the negative correlation between this disease and the human stature, the most interesting of which (in our opinion) states that stature maximization in both childhood and adolescence as the integral indicator of health can minimize (or even delay) dementia in the elderly (1892 cases) (Beeri et al, 2005) (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Our primary keyword search produced the article (Malek et al, 2009) on the somatotropin-based treatment of some complications of sporadic AD (Turnaev et al, 2016). In addition, our secondary keyword search yielded a lot of articles on the negative correlation between this disease and the human stature, the most interesting of which (in our opinion) states that stature maximization in both childhood and adolescence as the integral indicator of health can minimize (or even delay) dementia in the elderly (1892 cases) (Beeri et al, 2005) (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…However, in this regard, more studies have been done on IGF-1, but synaptic functions of GH are independent of IGF-1, and the separate effects of GH still need to be evaluated 22 . Previous studies in our laboratory have shown that intrahippocampal and peripheral injection of GH or IGF-1 can attenuate spatial learning deficit in a dose-dependent manner in NBM-lesioned aged rats 15,23 . The purpose of this study was to assess the direct central actions of GH on electrophysiological properties of hippocampal neurons.…”
mentioning
confidence: 78%
“…NBM lesioning: rats were anesthetized with an intraperitoneal injection of ketamine (100 mg.kg -1 body weight) and xylazine (10 mg.kg -1 body weight) 15 . The animals were placed in a stereotaxic frame, lesions were made by injecting ibotenic acid bilaterally (0.5 μg.0.1 μl -1 distillate water on each side for 5 min, Sigma-Aldrich Chemical Co., USA) into the NBM according to the rat brain atlas (AP; -1.3, L; ±2.3, V; -6.6) 24 .…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Baicalin has also been reported to preserve heat shock protein 70 (HSP70), with the latter being known to exert protective effects in neurons [2527]. S. baicalensis as such has been shown to exhibit memory enhancing properties against ibotenic acid (toxin), chronic lipopolysaccharide infusion, gamma-irradiation, beta amyloid proteins, ischemia, and so forth [2831]. Ethanol extract of Scutellaria baicalensis Georgi prevents oxidative damage and neuroinflammation and memorial impairments in artificial senescence mice [32].…”
Section: Discussionmentioning
confidence: 99%